The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/978-3-031-27007-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Is the First Language a Resource, an Obstacle, or Irrelevant for Language Minority Students’ Education?

Abstract: Successful integration into the education system is of major importance for the future prospects of immigrants and their children as well as for the social cohesion and viability of the receiving societies. Language is generally viewed as an important aspect of this integration. Whereas there is widespread agreement that the language of the residence country (L2) is crucial for students’ educational success, the relevance of the language of the country of origin (L1) is disputed. Adopting an interdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Relatedly, it might be that first-generation immigrant and refugee children in these classrooms do not feel the urge to assimilate, but they can instead navigate between the family’s and school’s cultures. The emphasis on children’s family language is important, as research showed that fostering children’s first language can also enhance their school achievement (Edele et al, 2023; Kirss et al, 2021). Moreover, this can indirectly promote German reading comprehension (Edele & Stanat, 2016), but effects may be delayed and not be visible in elementary school yet.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, it might be that first-generation immigrant and refugee children in these classrooms do not feel the urge to assimilate, but they can instead navigate between the family’s and school’s cultures. The emphasis on children’s family language is important, as research showed that fostering children’s first language can also enhance their school achievement (Edele et al, 2023; Kirss et al, 2021). Moreover, this can indirectly promote German reading comprehension (Edele & Stanat, 2016), but effects may be delayed and not be visible in elementary school yet.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that in classrooms where heritage and intercultural learning is enhanced, multilingualism plays an important role (Schachner, 2019). Research showed that fostering children's first language can also enhance their school achievement (Edele et al, 2023;Kirss et al, 2021). Thus, while reading comprehension in the school language might be diminished, there might be a stronger appreciation of children's first language skills.…”
Section: Cultural Diversity Climate and Children's Adjustmentmentioning
confidence: 99%